Multilayered polycrystallization in single-crystal YSZ by laser-shock compression. (13th July 2015) - Nishimura, Yasuhiko; Kitagawa, Yoneyoshi; Mori, Yoshitaka; Hioki, Tatsumi; Azuma, Hirozumi; Motohiro, Tomoyoshi; Komeda, Osamu; Ishii, Katsuhiro; Hanayama, Ryohei; Sekine, Takashi; Sunahara, Atsushi; Kajino, Tsutomu; et al.
Abstract: A single shot of an ultra-intense laser with 0.8 J of energy and a pulse width of 110 fs (peak intensity of W cm −2 ) is divided into two beams and the two beams counter-irradiated onto a 0.5 mm-thick single crystal yttria-stabilized zirconia (YSZ), changing the YSZ into a multilayered polycrystalline state. The laser-driven shock wave of the intensity 7.6 Pa penetrated the crystal as deep as 96 m, causing formation of a four-layered structure (the first layer from the surface to 12 m, the second from 12 to 28 m, the third from 28 to 96 m, and the fourth from 96 to 130 m, respectively). The grain size of the first layer was 1 m, while that of the second layer was broken into a few tens nanometers. The grain size of the third layer was a few hundred nanometers to a few ten micrometers. The area deeper than 96 m remained as a single crystal. The plasma heat wave might remelt the first layer, resulting in the grain size becoming larger than that of the second layer. The surface polycrystallization seems to maintain the residual stresses frozen in the film thickness direction. Our experimentally observed spatial profile of the grain size can be explained by this shock and heat waves model.